Perancangan Sistem Informasi Jasa Dan Pelayanan Kalibrasi Berbasis Website Menggunakan Metode Agile (Studi Kasus : Pusat Sarana Pengendalian Lingkungan Hidup) - Hakim Alanuari, Alif; Harits, Abdurrahman (PT Jurnal Cendekia Indonesia, 2026)
The Environmental Control Facility Center (PUSARPEDAL) service is a national reference laboratory that provides calibration services for environmental equipment. However, the process of administration and data management of calibration services that are still carried out manually or using Microsoft Excel causes a lack of efficiency, potential recording errors, service delays, and limitations in data integration between parts. This research aims to design and develop a website-based service information system and calibration services using the Agile method to improve effectiveness, accuracy, data security, and service quality. The research methods used include observation, interviews with service staff, and literature studies to identify system needs. System development is carried out iteratively using the Agile approach through the stages of planning, design, development, testing, deployment, and review. The system design is modeled using Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), while the system testing is carried out using the Black Box Testing method to ensure the suitability of functionality to user needs. The results of the study showed that the developed information system was successfully implemented with a functional success rate of 100% based on testing. The system is able to integrate service processes ranging from application submission, customer data and tool management, calibration status tracking, to digital certificate issuance. The implementation of this system has been proven to improve administrative efficiency, data management accuracy, service transparency, and ease of access to information for users. with high ticket volumes, with suggestions for further development such as AI integration for ticket prioritization.